2008
DOI: 10.1021/ol800576w
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Synthesis of Esters from Ketones. Alkyl Group as a Leaving Group

Abstract: The conversion of ketones to esters has been achieved through the use of Cu catalyst and tetrabutylammonium nitrite. This reaction involves the activation of the less activated C-C bond, and the alkyl group is removed as a leaving group. Various isopropyl ketones are found to be good substrates for this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…n-Butyl 4-tert-butylbenzoate (3na): [23] Yield 78% (18.3 mg); 1 H NMR (600 MHz, CDCl 3 ) δ: 8.05~7.90 (m, 2H), 7.51~7. 38 (m, 2H), 4.31 (t, J=6.6 Hz, 2H), 1.84~1.67 (m, 2H), 1.56~1.43 (m, 2H), 1.34 (s, 9H), 0.98 (t, J=7.4 Hz, 3H); 13 C NMR (151 MHz,CDCl 3 ) δ: 166.7,156.4,129.4,127.8,125.3,64.6,35.1,31.1,30.8,19.3,13.8.…”
Section: Activity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…n-Butyl 4-tert-butylbenzoate (3na): [23] Yield 78% (18.3 mg); 1 H NMR (600 MHz, CDCl 3 ) δ: 8.05~7.90 (m, 2H), 7.51~7. 38 (m, 2H), 4.31 (t, J=6.6 Hz, 2H), 1.84~1.67 (m, 2H), 1.56~1.43 (m, 2H), 1.34 (s, 9H), 0.98 (t, J=7.4 Hz, 3H); 13 C NMR (151 MHz,CDCl 3 ) δ: 166.7,156.4,129.4,127.8,125.3,64.6,35.1,31.1,30.8,19.3,13.8.…”
Section: Activity Testmentioning
confidence: 99%
“…n-Butyl 1-naphthoate (3pa): [23] Yield 74% (16.9 mg); 1 H NMR (600 MHz, CDCl 3 ) δ: 8.91 (d,J=8.7 Hz,1H),8.18 (d,J=7.2 Hz,1H),8.01 (d,J=8.2 Hz,1H),7.88 (d,J= 8.1 Hz,1H), 7.64~7.58 (m, 1H), 7.53 (t, J=7.5 Hz, 1H), 7.52~7.47 (m, 1H), 4.43 (t, J=6.7 Hz, 2H), 1.96~1.71 (m, 2H), 1.66~1.38 (m, 2H), 1.01 (t, J=7.4 Hz, 3H); 13 C NMR (151 MHz, CDCl 3 ) δ: 167.7, 133.9, 133.2, 131.4, 130.0, 128.5, 127.7, 127.6, 126.2, 125.9, 124.5, 65.0, 30.9, 19.4, 13.8.…”
Section: Activity Testmentioning
confidence: 99%
“…Traditionalm ethods of synthesis of esters have long been replaced by the more efficient and selective processes involving the use of coupling reagents, [3] organo-catalysts, [4,5] lewis-acid catalysts, [6,7] ionic liquids [8] as well as transition metal catalysts.A mongst these methods, transition metal-catalyzed oxidative esterification has played ap ivotalr ole in providing an efficient and mild synthetic strategy for obtaining these diverse structural motifs. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Earliest example for the oxidative esterification of primary alcohols was reported by Milstein andc o-workersu sing ruthenium-based catalytic system, [25] thus providing the required impetust ot he research community for further exploration. This was followed by a series of reports involving transition metal catalyzed oxidative esterification of alcohols to give dimerice sters.…”
mentioning
confidence: 99%
“…Next, we turned our attention to analyze the effect of base employed as the optimizations tudies revealed that the use of Na 2 CO 3 was necessary for providing an optimum yield of the product (Entry 14, Ta ble 1) in comparison to other bases (Entry [15][16][17][18][19][20].Any change in temperature failed to increaset he yield of the ester product as 80 8Cw as found to be the most suitable (Entry 23). Improvement in yield was observed with an increasei nr eactiont ime to 36 h( Entry 28) and further to 48 h (Entry 29).…”
mentioning
confidence: 99%
“…In the past few years, the synthesis of alkyl benzoate derivatives starting from aldehydes and ketones has been developed. 6,7 However, less attention has been paid to the synthesis of aryl benzoate derivatives. Thus, from a synthetic point of view, it is a highly desirable goal to develop a versatile approach for the synthesis of aryl benzoate derivatives in a simple way.…”
mentioning
confidence: 99%